PC-based software for thermal design of helixchanger heat exchangers - Fong, Lin Qiang (2015)
Shell-and-Tube Heat Exchangers with segmented baffles have proven to be versatile and efficient through years of industrial use. The invention of helical baffles was aimed to improve the existing segmented ones with benefits such as lower pressure drop per heat transfer unit with reduced vibration. However, due to its proprietary nature, Shell-and-Tube Heat Exchangers with Helical Baffles also called Helixchanger Heat Exchangers is rarely reported in the open literature. Due to its exclusiveness, Helixchanger Heat Exchanger design methods are not easily available in the public domain. Therefore, it is difficult for students or practising engineers to learn. Fortunately, Shinde et al. [1] [2] have come out with an alternative method of design calculations that was modified from the Bell- Delaware and Kern’s methods for calculating Segmented Shell-and-Tube Heat Exchangers. Both methods are well-established calculation methods adopted in many texts for teaching and actual calculation. This project makes use of the modified Bell-Delaware and Kern’s method to size Helixchanger Heat Exchangers. The executable software provides the user with the choice of either the “Learner” or the “Advanced” mode. With the “Learner” mode, there is a step-by-step guide for the user to learn how each method works, whereas in the “Advanced” mode, the user simply keys in the data and results can then be generated. The results from the software developed by the author have been validated by manual calculations and can be exported as a report in PDF format for future reference.